Naphthalene metabolism by pseudomonads: purification and properties of 1,2-dihydroxynaphthalene oxygenase. - Patel, T R (1980)
1,2-Dihydroxynaphthalene oxygenase was purified from Pseudomonas putida NCIB 9816 grown on naphthalene as the sole source of carbon and energy. The enzyme had a subunit molecular weight of 19,000 and in a medium containing phosphate buffer, 1 mM mercaptoethanol, and 10% (vol/vol) ethanol had a native molecular weight greater than 275,000. The enzyme required Fe2+ for activity. It was inactivated slowly on standing, and inactivation was accelerated by dilution with aerated buffers and by H2O2. Bathophenanthroline sulfonate, o-phenanthroline, 8-hydroxyquinoline, and 2,2'-dipyridyl also inhibited the enzyme. The inactive enzyme was reactivated by anaerobic incubation with ferrous sulfate and ferrous ammonium sulfate. Thiol reagents and acetone, ethanol, or glycerol decreased the rate of loss of activity. The enzyme was most active with 1,2-dihydroxynaphthalene, for which the Km was 2.8 X 10(-4) M. 3-Methyl- and 4-methylcatechols were oxidized at 3 and 1.5%, respectively, of the rate of 1,2-dihydroxynaphthalene, and the Km for 3-methylcatechol was 1.5 X 10(-4) M. Purified 1,2-dihydroxynaphthalene oxygenase catalyzed the oxidation of 1,2-dihydroxynaphthalene, leading to the appearance of 2-hydroxychromene-2-carboxylic acid, but 3-methylcatechol was oxidized by this enzyme to 2-hydroxy-6-oxoheptadienoic acid. Thus, a product structurally analogous to 2-hydroxychromene-2-carboxylic acid was not observed when 3-methylcatechol was oxidized. This may indicate that 2-hydroxychromene-2-carboxylic acid results from cyclization of a ring fission product before release from the enzyme.